A Narrative Analysis of University Students’ Alcohol Stories in Terms of a Fryeian Framework (European Journal of Mental Health, 2007)
If the marketing profession is outstanding at relying on or creating new myths in order to attain commercial goals then the question follows whether myths could also be used for social marketing campaigns. The aim of this article is to introduce what alcohol consumption means for today’s university students and what their related stories are like. We argue that the motifs found in authentic texts can be used when designing and implementing social marketing actions. Consequently, the present research primarily draws on narrative analysis. 146 alcohol consumption stories and 134 alcohol advertisement narratives were analysed. The article presents a structural analysis of students’ alcohol consumption stories, using Northrop Frye’s taxonomy of mythoi to assign consumer narratives to four categories: comedy, romance, tragedy, and irony. Although we are in possession of a large amount of knowledge about how science and logical thinking works, we know little about how to construct good stories. In this article a didactic introduction of Frye’s system will follow, whilst we will continue to look for ‘good’ stories. This study aims to provide the reader with a structured tool inventory (charts, stories), from which one will be free to choose, but at the same time one should take care to retain one’s own creativity and produce credible stories.